1998
DOI: 10.4037/ajcc1998.7.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of critical care physicians and nurses to handle requests for organ donation

Abstract: BACKGROUND: Critical care nurses and physicians usually care for those patients whose condition progresses to brain death and are also often responsible for requesting organ donation from the family of a brain-dead patient. We hypothesized that staff support, knowledge, and training levels would be significantly associated with organ donation rates. OBJECTIVE: To assess the readiness of critical care staff to successfully handle requests for organ donation. METHODS: A total of 1061 critical care staff from 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 0 publications
2
32
1
1
Order By: Relevance
“…The results revealed that ICU nurses rated their perceptions of their theoretical knowledge about aspects of the donor process, such as death diagnostics, procedures and the donor operation as low. This is similar to findings in other studies (Evanisko et al 1998, Bøgh & Madsen 2005, Chernenko et al 2005. Relatives' fear of desecration of the body might be relevant to their decision about organ donation (Sanner 2007, Siminoff et al 2007, Sque et al 2008.…”
Section: Discussion Of the Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The results revealed that ICU nurses rated their perceptions of their theoretical knowledge about aspects of the donor process, such as death diagnostics, procedures and the donor operation as low. This is similar to findings in other studies (Evanisko et al 1998, Bøgh & Madsen 2005, Chernenko et al 2005. Relatives' fear of desecration of the body might be relevant to their decision about organ donation (Sanner 2007, Siminoff et al 2007, Sque et al 2008.…”
Section: Discussion Of the Resultssupporting
confidence: 88%
“…Educational input was seen as essential for approaching the family; however, only one-third of the respondents had any training in this difficult task (Evanisko et al 1998). In Evanisko et al's (1998) study the educational level of staff was higher at hospitals with higher donor rates. Chernenko et al (2005) found that lack of knowledge about transplantation, donor criteria and guidelines was an impediment to donor identification and organ preservation.…”
Section: Icu Nurses' Professional Competence In the Organ Donor Processmentioning
confidence: 86%
See 3 more Smart Citations